Tailored Lattice Compressive Strain of Pt-Skins by the L12 -Pt3 M Intermetallic Core for Highly Efficient Oxygen Reduction - Wang, Zichen (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.